Citrus peel flour as an ingredient for the meat industry - Velasquez-Rivera, Jorge Ruperto; Díaz-Torres, Raúl (Agronomía Mesoamericana, 2024)
Introduction. Citrus fruits, particularly orange (Citrus sinensis) and mandarins (Citrus reticulata), are among the most widely consumed globally. However, their industrial processing generates a significant amount of byproducts, which are important source of valuable bioactive substances. Among the most abundant byproducts are peels, which contain high levels of compounds with antioxidant and antimicrobial activity, as well as fiber. Objective. To describe the potential benefits of using of citrus peels as a source of bioactive compounds and their applications as ingredients in developing healthier meat. Development. This review analyzed the main characteristics of citrus fruit peels, emphasizing their chemical composition, physical properties, and value as a source of a bioactive compounds. The effects reported in scientific literature regarding their use as ingredients in meat products were also examined. The discussions focuses on changes introduced in the chemical, sensory, textural, color, and durability characteristics of meat products. These changes have been attributed to the presence of bioactive compounds with antioxidant and antimicrobial properties, including aromatic components, polyphenols-flavonoids, essential oils, pigments, carbohydrates, and dietary fibers. The benefits of these compounds vary depending on their origin, concentration, and method of incorpation. Conclusion. The industrialization of citrus fruits generates large quantities of byproducts rich in bioactive compounds with antioxidant and antimicrobial properties. These byproducts present a viable alternative for developing healthier and more sustainable meat products with suitable sensory properties and extended shelf life. However the specific characteristics of the byproduct and the food matrix where it is intended to be used must be considered in each case.